A Legal Analysis of Police Investigation Procedures for Corporate Crimes in the Cirebon Region - Akmal Muzhafar Rasul; Alip Rahman (Journal of Social Research, 2026)
Corporate crimes in Indonesia, particularly corruption in regional public companies, remain a significant challenge to governance and financial accountability. In the Cirebon region, cases at the Regional Drinking Water Company (Perusahaan Daerah Air Minum, PDAM) revealed large-scale misuse of funds by employees, including falsification of financial records, forgery of signatures, and diversion of state assets into illicit investment activities, resulting in losses exceeding IDR 3.7 billion. This study aims to analyze police investigation procedures for corporate crimes, focusing on the application of legal provisions regarding corporate criminal liability and identifying gaps between written law and investigative practices. A normative legal approach was employed, combining legislative review, conceptual analysis, and case studies of court decisions, supported by observations of police investigation processes and literature review. Results indicate that while the Criminal Procedure Code and Corruption Eradication Laws provide a legal basis to prosecute corporations, investigative practice tends to prioritize individual liability over corporate accountability. Challenges include complex organizational structures, insufficient technical guidelines, and difficulties in attributing corporate guilt. Consequently, enforcement is inconsistent, and the deterrent effect of corporate criminal liability is limited. The study concludes that strengthening regulations, providing detailed technical guidance, and enhancing investigator capacity are critical to achieving legal certainty, justice, and effective prevention of corporate corruption.